Towards more Reflective Teacher Education Mediations and Barriers - Ghosh, Kavita (JOURNAL OF INDIAN EDUCATION, 2015)
The multifarious benefits of making ‘Reflection’ a core guiding factor in teacher education are well articulated in recent literature. It is not only desirable but almost essential to create reflective prospective teachers who can deal with the complexities of the field of education. Various pertinent perspectives have come to fore in last few decades that attempt to understand the phenomenon of ‘reflection’ and attempts have also been made to understand the relevance of ‘reflection’ particularly in the context of teacher education. It becomes important that teacher education programmes make informed choices on the basis of these theoretical perspectives and at the same time give careful considerations to the research findings that talk of reflection in teacher education. It is only then we can stay assured that efforts have been made to make teacher education a reflective practice rather than a mere skill and knowledge delivering endeavour.